2021
DOI: 10.1186/s13293-020-00347-y
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in expression of immune elements emerge in children, young adults and mice with osteosarcoma

Abstract: Background Males < 40 years old are more likely to be diagnosed with and die from osteosarcoma (OS). The underlying mechanisms may depend on sex differences in immune response. Methods We used SEER data to estimate survival differences between males and females aged < 40 years at OS diagnosis. In NCI TARGET-OS cases, we determined sex differences in gene expression, conducted Gene Set Enrichment Analysis (GSEA), and applied the LM22 signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…CIBERSORT is a deconvolution method applied for the characterization of cell composition of a complex tissue (Peng et al, 2021). LM22 is a leukocyte gene signature matrix that contains the expression levels of 547 genes for distinguishing 22 human hematopoietic cell phenotypes (Mills et al, 2021). In this study, CIBERSORT combined with LM22 signature matrix were used to quantify the infiltration levels of twenty-two immune cells in OSCC.…”
Section: Consensus Clustering For Tumor Immune Microenvironment Cellsmentioning
confidence: 99%
“…CIBERSORT is a deconvolution method applied for the characterization of cell composition of a complex tissue (Peng et al, 2021). LM22 is a leukocyte gene signature matrix that contains the expression levels of 547 genes for distinguishing 22 human hematopoietic cell phenotypes (Mills et al, 2021). In this study, CIBERSORT combined with LM22 signature matrix were used to quantify the infiltration levels of twenty-two immune cells in OSCC.…”
Section: Consensus Clustering For Tumor Immune Microenvironment Cellsmentioning
confidence: 99%
“…This increased prevalence of OS among males has been consistently reported for several different races as well [12]. Furthermore, many studies found male OS patients to have worse 5-year [12][13][14][15][16] or event-free [17] survival compared to females. In fact, males with OS have a higher incidence of distant disease and metastases compared to female patients [13] and may be less sensitive to chemotherapy as seen in similar cancers [18].…”
Section: Introductionmentioning
confidence: 54%
“…Furthermore, many studies found male OS patients to have worse 5-year [12][13][14][15][16] or event-free [17] survival compared to females. In fact, males with OS have a higher incidence of distant disease and metastases compared to female patients [13] and may be less sensitive to chemotherapy as seen in similar cancers [18]. OS also tends to affect patients during periods of rapid growth.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma, a bone tumor displaying a bimodal peak in incidence during the teen and late adult years [72], and soft tissue malignancies were found to be more common in male populations than in females across every race/ethnicity group, with an overall ratio of males to females computed at 1.3:1. Specifically, the incidence rate for males was 8.1 (with a 95% confidence interval of 7.7-8.6) compared to an incidence rate of 6.2 for females (with a 95% confidence interval of 5.8-6.6) [73].…”
Section: Sex-and Gender-specific Physiopathology Of Orthopedic Malign...mentioning
confidence: 99%